Тhe Digital Transformation in the Hospitality Industry: Realities, Trends, Perspectives - Bulican, Adrian (Journal of Danubian Studies and Research, 2023)
Today’s trend is the digital economy. Digitization processes are particularly relevant for the services sector. Both large and small companies in the hotels, passenger transport, catering, leisure sectors use a varied set of communication tools (hardware and software) to organize the business process. The phenomenon of digitization is no stranger to the hospitality industry in Moldova. Hotels in Chisinau are exploiting the advantages of online presence and the tools that operating on the Internet and Web 2.0 platform brings.